PORTFOLIO OPTIMIZATION FOR SHIPPING & DELIVERY SERVICES WITH R: BEFORE AND AFTER PANDEMIC COVID-19 - Anggraeni, Dina; Sugiyanto, Kris; Zam Zam, M. Irwan; Patria, Harry (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The objective of this research is to construct an optimum investment portfolio of courier services sector stocks during period 2018-2021 using Modern Portfolio Theory model and to analyse risk and return generated by optimal portfolio before and after Covid-19 using R programming. Furthermore, we would also examine the impact of the Covid-19 on stock prices before and after Covid-19 to formulate investment decisions. The sample are 5 biggest courier services stocks (by market capitalization) that are listed consistently and did not stock split or reverse stock and the number of observations in 4825 stocks prices during the period January 2018 to October 2021. Based on the result of optimum investment research, we can observe that the best performing stocks with high tangency is AMZN, in fact way ahead of other sample emitens. The result will be expected to help investors to bid the best possible portfolio in courier services.